2021
DOI: 10.3390/su13042302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of Ecosystem Service Value in the Zhoushan Islands Based on LUCC

Abstract: Islands are the confluence of terrestrial ecology and marine ecology. With urban expansion and economic development, the ecological environment of islands is facing serious threats. In order to study the island area land use change/cover (LUCC) and its impact on the ecosystem service value (ESV), this study was conducted. This study evaluated the ESV of Zhoushan Islands based on the LUCC, using the equivalent coefficient method, and simulated and analyzed the ESV of Zhoushan Islands in 2025 under different sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In general, drastic changes in land-use models can harm ecosystems (Qiao et al, 2020;Deng et al, 2021;Xi et al, 2021). The sustainable development of cities cannot be achieved without Frontiers in Environmental Science frontiersin.org natural ecosystems such as water and grassland areas during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…In general, drastic changes in land-use models can harm ecosystems (Qiao et al, 2020;Deng et al, 2021;Xi et al, 2021). The sustainable development of cities cannot be achieved without Frontiers in Environmental Science frontiersin.org natural ecosystems such as water and grassland areas during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem services are a general term for products or services that can be directly or indirectly provided to human beings in the structure, function, or process of the ecosystem (Costanza et al, 2014 ; Daily et al, 2000 ), such as providing raw materials, purifying the environment, and maintaining biological properties (Jing et al, 2021 ), which is an essential foundation for ensuring the stability as well as sustainable development of the regional ecological environment (Reid et al, 2005 ; Xi et al, 2021 ). However, due to human activities such as industrialization (Opoku & Aluko, 2021 ), rapid population expansion (Dimnwobi et al, 2021 ), and excessive consumption of resources (Mittal & Gupta, 2015 ), global ecosystem services have been seriously damaged (Chen et al, 2019 ; Costanza et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of land use, Xi, et al [ 23 ] analyzed the spatiotemporal characteristics of the ESV of island cities based on land use/cover and predicted future ESV. Rahman and Szabó [ 24 ] analyzed the impact of land use/cover change (LUCC) on the value of urban ES in Dhaka, Bangladesh, and found that water areas contributed the most to ESV.…”
Section: Introductionmentioning
confidence: 99%